MODELING OF SEDIMENT TRANSPORT IN PANARUKAN PORT, SITUBONDO, EAST JAVA - Fuad, Mochamad Arif Zainul; Wardani, Aisy Nur Isna (Directorate of Research and Community Service (DRPM), 2024)
Sedimentation presents a significant challenge in port management. It poses a risk to arriving and departing ships, potentially causing them to sink. The shallowing of the previous port required the construction of the new Panarukan port pier. This project focuses on using sediment transport modeling to analyze sediment transport patterns, and measure the extent of sedimentation or erosion at Panarukan Harbor. The sediment transport modeling utilizes the MIKE 21 program, which includes various modules such as the hydrodynamic module, the spectral wave module, the sand transport module, and the mud transport module. The data used in this modeling includes depth information, coastline data, wave height and period measurements, river water discharge data, total suspended solids (TSS) measurements, and the average sediment grain size. The modeling was carried out over a five-month period during the rainy season, starting in October 2019 and ending in February 2020. Based on the modeling results, sedimentation occurred at the Sampean River Estuary, causing a significant increase in the bed level of 0.4 meters during the rainy season. The sediment transport pattern of the Sampean River Estuary is characterized by a flow rate of -4200 to 3600 m2/s towards the coast and a flow rate of -2800 to 2800 m2/s perpendicular to the coast. The movement of sediment in the water differs between high and low tides. The concentrations of Total Suspended Solids (TSS) vary from 0.01 to 0.13 kg/m3 or 10 to 130 mg/l.